Can we still avoid dangerous climate change - Chapter on Negative Emissions Technologies - Shah,N; McGlashen,N (Springer, 2012)
“The AVOID programme integrates, quantifies and communicates”Governments are faced with decisions regarding our future climate. The science is telling them that the climate is unequivocally changing, that the impacts will be felt across the world, and that something must be done....But to take appropriate measures, Governments need to understand the consequences of such measures and they need to do so based on sound scientific evidence. There are three core questions that need addressing:•What level of climate change is potentially dangerous? •What emission reductions will avoid dangerous climate change? •What is the technical and economic feasibility of such emission reductions?